Pengaruh Biaya Produksi, Biaya Promosi, dan Penjualan terhadap Laba Bersih - Maulana, Fadjar; Adiyanto, Mochamad Reza (Management Department of Economics and Business Of Trunojoyo Madura University, 2025)
This study aims to analyze the effect of production costs, promotion costs, and sales on net profit in cosmetic and household goods sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019–2023 period. This study uses a quantitative approach with a population consisting of six companies that meet the purposive sampling criteria. Data were obtained from the company's financial statements published on the IDX. Data analysis was carried out using the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS) using SmartPLS software. The results of the study show: (1) Production costs do not have a significant effect on net profit. (2) Promotion costs have a negative and significant effect on net profit. (3) Sales have a positive and significant effect on net profit. (4) Simultaneously, production costs, promotion costs, and sales have a significant effect on net profit with an R² value of 0.970, indicating that the three variables are able to explain 97% of the variation in net profit. These findings provide practical implications for companies in optimizing sales strategies and promotion cost efficiency to increase profitability.